Greenwashing. A risky bet for the positioning of a green brand. - González Arredondo, Ana Sofía (2020)
Abstract: There is no doubt that one of the primary objectives of a marketing campaign is to position or reposition a good or service in the minds of its consumers. However, what happens when the technique used turns out to be perceived as a deceptive action? Greenwashing is a technique that some companies have used in recent years to consider themselves as green brands, even if this means proposing actions that are not consistent with their production policies. Thus, this article seeks to make a theoretical approach to green marketing and greenwashing, seeking to reflect on conscious consumers and how these types of actions can be counterproductive for the new generations of buyers when brands are pointed out as incongruent, affecting their reputation and image.